miRNA Signature in Early-stage Mycosis Fungoides - Sissel T. Sørensen; Thomas Litman; Maria Gluud; Pamela Celis; Sara Torres-Rusillo; Andreas Willerslev-Olsen; Niels Ødum; Lars Iversen; Lise M. Lindahl (Medical Journals Sweden, 2022)
Altered miRNA expressions are assigned pathogenic properties in several cancers including mycosis fungoides and could play a role in the early onset of the disease. The aim of this study was to examine disease-specific miRNA expression in early-stage mycosis fungoides patch and plaque lesions. A quantitative real-time PCR platform of 384 human miRNAs was used to study miRNA expression in 154 diagnostic mycosis fungoides biopsies. A total of 110 miRNAs were significantly differentially expressed (>2-fold, p < 0.05) between plaque lesions and healthy controls, and 90 miRNAs (>2-fold, p < 0.05) differed between patch lesions and healthy controls. Moreover, 13 miRNAs differed in expression between patch and plaque lesions. Early-stage mycosis fungoides exhibited miRNA features that overlapped with those of psoriasis. However, 39 miRNAs, including miR-142-3p, miR-150 and miR-146b, were specific to mycosis fungoides. In conclusion, early-stage mycosis fungoides expresses a distinct miRNA profile, indicating that miRNAs could play a role in the early development of mycosis fungoides.